KAJIAN KARAKTERISTIK PETANI KARET DALAM MENENTUKAN PILIHAN KELEMBAGAAN TATANIAGA DI PROVINSI ACEH - Bakar, Basri A; Fauzi, Emlan (Jurnal AGRISEP, 2013)
Determining on rubber marketing institutional options is influenced by the characteristics of the institutional and socio-economic of farmers. This study aimed to examine the role of the characteristics of rubber farmers in the establishment of marketing institutional options. The research was conducted by survey method. The research has been taken in two districts of West Aceh and East Aceh. The numbers of respondents were 360 farmers. Data collection was taken by observation and structured interviews to a number of "key informants" and performed Focus Group Discussion (FGD) in strengthening and completing the information required. The results show the magnitude of institutional partnership opportunities for farmers to choose the traditional institutional was significantly influenced by the negative direction by the experience of farmers in rubber farming, farmers formal education, number of family member, and number of tapped rubber trees; and significantly and positively influenced by non-formal education and total family income. Total family income has an elastic response.